The influences of Cs+ substitution and direct doping on the phase evolution, microstructure and electrical properties of KNNT ceramics - Surirat Yotthuan; Thanya Udeye; Naratip Vittayakorn; Sukum Eitssayeam; Phieraya Pulphol; Theerachai Bongkarn (Ferroelectrics, 2022)
The effects of Cs+ substitution and direct doping in (K0.5Na0.5)(Nb0.7Ta0.3)O3 (KNNT) ceramics, on the crystal structure, microstructure and electrical properties were investigated. Both the KNNT with Cs+ substitution (K0.5-xCsxNNT) and addition (KNNT-xCs) (x = 0, 0.01, 0.02, 0.03 and 0.04 mol%) were synthesized by the solid-state combustion technique using glycine as fuel. All samples were sintered at 1130–1150 °C for 4 h. The x-ray diffraction (XRD) analysis for the ceramics revealed the presence of orthorhombic (O) and tetragonal (T) phases in all samples. Increasing both the Cs+ substitution and doping amounts, enhanced the content of orthorhombic phase, as verified by the Rietveld refinement technique. It was found that Cs+ doping, either substitutional or additional, strongly decreased their density, dielectric and ferroelectric properties. The undoped KNNT ceramic exhibited well-saturated P-E hysteresis loop. With Cs+ doping, the samples became unsaturated and a leakage current was produced. The KNNT-xCs ceramics demonstrated higher density and dielectric properties than the K0.5-xCsxNNT ceramics.
Keywords: Ferroelectric and Piezoelectric Materials; Microwave Dielectric Ceramics Synthesis; Dielectric properties of ceramics